DISCUSSIONS AND REFL ECTIONS ON THE ECONOMIC CRISIS IN TARAPACÁ (1934 - 1953): PRELIMINARY NOTES. - Donoso Rojas, Carlos (Revista de Historia Social y de las Mentalidades, 2011)
The present article presents a sketch of the social and economic situation of province of Tarapacá during the cycle of force of the Institu to de Fomento Minero e Industrial, organism  created to promote these areas in the region, after the collapse of the saltpetre. With an economy historically tied to the export of this mineral, discussion and proposals of political authorities and residents  in the region focused on the duality of strengthening the role of a subsidiary, or to  eliminate all kinds of barriers that were obstructing the free development of the regional economy.
Keywords: Tarapacá; State; Crisis